2020
DOI: 10.1080/1828051x.2020.1724523
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation profile and nutritional value of sesame silage compared to usual silages

Abstract: The objective was to evaluate the fermentation parameters, chemical composition and in situ degradability of sesame silage in comparison to usual silages. The losses, fermentation quality and chemical composition of the forages and silages were evaluated using a completely randomised design with four treatments (sesame, corn, millet and sunflower) and four replicates per treatment, the silages were produced in experimental silos. In-situ degradability was evaluated using a completely randomised design with fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
1
12
0
3
Order By: Relevance
“…Sunflower (Helianthus annuus L.) is an annual broadleaf crop belonging to the Asteraceae family, known worldwide for producing achenes and oil of the highest quality (KOUTROUBAS et al, 2020). This species has a great productive ability, being used for medicinal and ornamental purposes, silage and forage production, green manure, bioremediation, biofuel production, among others (HESAMI et al, 2015;AMORIM et al, 2020;IRAM et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Sunflower (Helianthus annuus L.) is an annual broadleaf crop belonging to the Asteraceae family, known worldwide for producing achenes and oil of the highest quality (KOUTROUBAS et al, 2020). This species has a great productive ability, being used for medicinal and ornamental purposes, silage and forage production, green manure, bioremediation, biofuel production, among others (HESAMI et al, 2015;AMORIM et al, 2020;IRAM et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…(2021) and Amorim et al . (2020), in order to obtain an adequate fermentation, a water-CHO content between 60 and 150 g/kg DM is needed. Although the CHO content in the plant was 119.1 g/kg DM (Table 1), it had high moisture, thus the haylage from in natura material had the lowest amount of CHO (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Nath et al (2018) found 32.29 g/kg DM of CHO in haylage of Tifton 85, while in the haylage of Marandu grass with 50-60% DM, higher values were observed. According to Silva et al (2021) and Amorim et al (2020), in order to obtain an adequate fermentation, a water-CHO content between 60 and 150 g/kg DM is needed. Although the CHO content in the plant was 119.1 g/kg DM (Table 1), it had high moisture, thus the haylage from in natura material had the lowest amount of CHO (Table 2).…”
Section: Chemical Composition Of the Haylagementioning
confidence: 99%
“…where, SWC = total silo weight at closure; SWO = total silo weight at opening; FMC = forage mass at closure; and DMCC = forage DM concentration at closure. Effluent losses (EL) were calculated using the equation proposed by Amorim et al (2020), based on the sand weight difference and the green matter mass at the closure: where, DMR = dry matter recovery rate; FMO = forage mass at opening; DMO = dry matter at the opening; FMC = forage mass at closure; and DMC = dry matter at closure.…”
Section: Determination Of Fermentation Losses Of Silagesmentioning
confidence: 99%
“…Therefore, alternatives are necessary to meet the demand for forage in this period. Thus, the storage of surplus forage as silage, during the rainy period for use in the dry period, is a viable strategy to guarantee the supply of high-quality feed to animals during the period of food shortage (Amorim et al, 2020).…”
Section: Introductionmentioning
confidence: 99%